A Fundamental Investigation of the Caro’s Acid Cyanide Destruction Process - A. M. Simons (Canadian Institute of Mining, Metallurgy and Petroleum, 2014)
Cyanide destruction by Caro’s acid is one process commonly employed by gold operations to meet regulatory requirements and/or the International Cyanide Management Code compliance for weak acid dissociable (WAD) cyanide in cyanidation tails or waste water from such operations. Typically smallscale bench tests to evaluate and assess the suitability of the Caro’s acid destruction process are conducted. Additionally, the experimental procedure used during these preliminary investigations may also differ from that implemented at the full-scale. This paper presents the results from a fundamental investigation of the Caro’s acid process to establish a more detailed understanding of the impact that the experimental procedure has on the destruction of cyanide. In particular, it was found that the control of pH was important to avoid copper(I) cyanide precipitation at low pH and maximise WAD cyanide destruction. Residual peroxide in the preparation of Caro’s acid has the potential for subsequent cyanide destruction and could be exploited.